2024
DOI: 10.1101/2024.04.01.587595
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cryo-electron tomographic investigation of native hippocampal glutamatergic synapses

Aya Matsui,
Cathy J. Spangler,
Johannes Elferich
et al.

Abstract: Chemical synapses are the major sites of communication between neurons in the nervous system and mediate either excitatory or inhibitory signaling [1]. At excitatory synapses, glutamate is the primary neurotransmitter and upon release from presynaptic vesicles, is detected by postsynaptic glutamate receptors, which include ionotropic AMPA and NMDA receptors [2, 3]. Here we have developed methods to identify glutamatergic synapses in brain tissue slices, label AMPA receptors with small gold nanoparticles (AuNPs… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…This study identified the existence of trans-synaptic nanocolumns, which co-organize the pre-synaptic release machinery in register with post-synaptic AMPARs and improve the efficiency of synaptic transmission [87,88] (figure 1b,c). Interestingly, the recent developments in cryo-electron tomography have allowed the ultrastructural visualization of these protein nanodomains and trans-synaptic assemblies [102][103][104][105][106][107][108]. The burning question that thus arose was: what are the underlying molecular elements that bridge pre-and post-synaptic nanodomains?…”
Section: Post-synaptic Nano-organization and Trans-synaptic Complexes...mentioning
confidence: 99%
“…This study identified the existence of trans-synaptic nanocolumns, which co-organize the pre-synaptic release machinery in register with post-synaptic AMPARs and improve the efficiency of synaptic transmission [87,88] (figure 1b,c). Interestingly, the recent developments in cryo-electron tomography have allowed the ultrastructural visualization of these protein nanodomains and trans-synaptic assemblies [102][103][104][105][106][107][108]. The burning question that thus arose was: what are the underlying molecular elements that bridge pre-and post-synaptic nanodomains?…”
Section: Post-synaptic Nano-organization and Trans-synaptic Complexes...mentioning
confidence: 99%